The equine diaphragm: A novel technique for repeatable ultrasound measurement. Issue 6 (17th August 2020) - Fitzharris, Laura E.; Meehan, Lucinda J.; Hezzell, Melanie J.; Allen, Kate J.
Abstract: The diaphragm is an important respiratory muscle, playing a key role during exercise. In humans, diaphragm thickness increases in response to training and is correlated with inspiratory strength. In order to assess respiratory strength in the horse, new evaluation techniques are required and measurement of diaphragm thickness, in a non‐invasive and repeatable manner, is a possible approach. The purposes of this four‐part, prospective, pilot study were to develop and describe a repeatable method to measure the diaphragm thickness, using ultrasonography, in Thoroughbred racehorses. A standardized technique was developed whereby the ultrasound transducer was positioned 1 cm below a line between the cranioventral aspect of the tuber coxae and olecranon. The diaphragm thickness was measured on three occasions 1 week apart, by a single observer to determine the intraobserver repeatability, and by a second observer on one occasion to assess interobserver reproducibility. The diaphragm was observed in all intercostal spaces (ICS) from 7 to 17 on the left side, and 6 to 17 on the right side in a single horse. The thickest measurement (1.42 cm), obtained from 11 horses, was at ICS 11 on the left‐side during inspiration. The narrowest measurement (0.56 cm) was obtained at ICS 16 on the right‐side during expiration. There was no significant difference between the measurements obtained by a single observer on three occasions ( P < .05). This is the first study to provide a detailed description of ultrasonographic imaging and measurement of the equine diaphragm. The novel technique developed to position the ultrasound transducer in a standardized location allowed examination and measurement of the diaphragm with good repeatability.